Impact of Moral Ethics on Consumers' Boycott Intentions: A Cross-Cultural Study of Crisis Perceptions and Responses in the United States, South Korea, and Singapore. (April 2021) - Shim, Kyujin; Cho, Hichang; Kim, Soojin; Yeo, Su Lin
This study investigates the effects of individuals' moral foundations on perceptions and responses to a company's crisis. Drawing on moral foundations theory, it empirically tests a theoretical model of crisis attribution and moral outrage with two antecedents (i.e., individualizing moral and binding moral) on three outcomes (i.e., crisis attribution, anger, and boycott intentions), using more than 3, 000 respondents from three culturally diverse countries—the United States, South Korea, and Singapore. The study finds that individualizing and binding moral foundations have significant effects on attribution, emotional reaction (i.e., anger), and behavioral intentions related to corporate irresponsibility, although their effects are distinct and varied across countries. While individualizing moral foundations lead to boycott intentions, the effects of binding moral foundations are multifaceted. Implications for communication professionals practicing in a highly globalized business environment today to recognize variations in morality among different publics in times of crisis are discussed.